PENGARUH FIRM SIZE DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN VARIABEL INTERVENING (Pada Perusahaan Manufaktur yang Terdaftar di JII Tahun 2021-2023) - Permatasari, Qisthoni; Lestari, Wuryaningsih Dwi; Achmad, Nur; Kuswati, Rini (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to examine the Effect of Firm Size and Leverage on Company Value with Capital Structure as an Intervening Variable (In Manufacturing Companies Listed in the Jakarta Islamic Index for the 2021-2023 Period). The population used in this study is manufacturing companies registered in JII for the 2021-2023 period. The sample used as many as 6 companies using descriptive statistical analysis methods. Data analysis technique using panel data regression with Fixed Effect method. The results showed that Firm Size and Leverage have a significant effect on the Capital Structure of manufacturing companies listed in the Jakarta Islamic Index (JII) 2021 – 2023, so the first hypothesis and the second hypothesis are accepted. Capital Structure, Firm Size have a significant effect on the Value of manufacturing companies listed in the Jakarta Islamic Index (JII) 2021 – 2023, then the third hypothesis and the fourth hypothesis are rejected. Leverage does not have a significant effect on the Value of manufacturing companies listed in the Jakarta Islamic Index (JII) 2021 – 2023, so the fifth hypothesis is rejected. Firm Size and Leverage do not have a significant effect on Company Value with capital structure as an intervening variable, so the sixth hypothesis and the seventh hypothesis are rejected. Keywords: Firm Size, Leverage, Company Value, Capital Structure, Manufacturing, JII